2023
DOI: 10.3389/fnut.2023.1167920
|View full text |Cite
|
Sign up to set email alerts
|

Association of fat-soluble vitamins (A, D, and E) status with humoral immune response to COVID-19 inactivated vaccination

Abstract: BackgroundFat-soluble vitamins (A, D, and E) are essential for the proper functioning of the immune system and are of central importance for infection risk in humans. Vitamins A, D, and E have been reported to be associated with the immune response following vaccination; however, their effects on the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination remain unknown.MethodsWe measured the neutralizing antibody titers against wild type and omicron within 98 days after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Despite some recent and important achievements, 22 , 23 , 24 there are still controversies about the effect of vitamin D status on antibody response after vaccination or infection. 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A study recruiting 97 healthcare workers found that individuals without VDD had an average of 29.3% higher peak antibody response induced by the first dose of the SARS‐CoV‐2 BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some recent and important achievements, 22 , 23 , 24 there are still controversies about the effect of vitamin D status on antibody response after vaccination or infection. 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A study recruiting 97 healthcare workers found that individuals without VDD had an average of 29.3% higher peak antibody response induced by the first dose of the SARS‐CoV‐2 BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some recent and important achievements, 22 , 23 , 24 there are still controversies about the effect of vitamin D status on antibody response after vaccination or infection. 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A study recruiting 97 healthcare workers found that individuals without VDD had an average of 29.3% higher peak antibody response induced by the first dose of the SARS‐CoV‐2 BNT162b2 vaccine. 23 Zelini et al observed a significant correlation between baseline serum 25(OH)D concentration and anti‐S neutralizing antibody response at 6 months after the second vaccination and concluded that adequate vitamin D levels could improve immune responses to mRNA vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite enormous scientific interest in exploring various aspects related to COVID‐19 vaccination, the potential association between micronutrients and humoral responses following COVID‐19 vaccination remains understudied. Only a limited number of studies with sample sizes ranging from 97 to 73 254 participants have investigated the associations between circulating concentrations of micronutrients, particularly those involved in immune regulation, and humoral immune responses as well as protection following inoculation with COVID‐19 vaccines 14‐25 . Three studies have reported no association between serum iron or selenium status, as well as concentrations of total zinc, and antibody concentrations or titers in response to COVID‐19 vaccinations 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have reported no association between serum iron or selenium status, as well as concentrations of total zinc, and antibody concentrations or titers in response to COVID‐19 vaccinations 14‐16 . Nine studies have reported the associations between serum vitamin D concentrations or status (sufficient, deficient, or insufficient) and humoral responses following COVID‐19 vaccinations, yet inconsistent conclusions have been reached 17‐25 . Investigations into the influence of micronutrients on antibody binding affinity and neutralizing capacity against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), crucial parameters for immune protection, are virtually non‐existent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation